Manual for treatment and control of lameness in cattle - Van Amstel, S. R. (Blackwell Pub., 2006)
The book includes up to date information on common lameness conditions of cattle and emphasizes the practical aspect of functional and corrective trimming. Additionally it covers the anatomy and pathology of the bovine foot with illustrations of anatomical features as well as detailed photographs of lesions.